Board independence, state ownership and stock return volatility during Chinese state enterprise reform - Zhang, Cheng; Cheong, Kee Cheok; Rasiah, Rajah (Emerald, 2018)
Purpose: This study aimed at investigating the influence of corporate governance on firm risk during the Chinese state enterprise reform. The purposes of this study are to examine the effects of board independence, state ownership and other governance variables on firm risk and to check the influence of controlling shareholder types on firm risk. Design/methodology/approach: This study uses the dynamic and static panel model to estimate the effects of board independence, state ownership and other governance factors on return volatility. To examine the influence of controlling shareholder types on corporate risk-taking, this study further used the treatment effect model (or sample selection model) to analyze the effect of private, state-owned enterprise (SOE) entity, central government and local government controls on corporate risk-taking. Findings: It was found that the enforcement of board independence significantly increases firm risk. The strategy of decentralizing state enterprises (from central government to local government) is a good way to achieve stable stock returns. Originality value: This study contributes to existing knowledge in several ways. First, it focused on independent directors rather than on the size of the corporate board. Second, it highlighted the impacts of state ownership and control on corporate risk. Instead of treating all types of state ownership as homogenous, SOEs are further classified into directly controlled and indirectly controlled, in line with prior studies.